Pembentukan Sendi-sendi Hukum Adat dalam Hukum Positif Indonesia - Iswantoro Iswantoro (UIN Sunan Kalijaga Yogyakarta, 2012)
The existence of traditional law has been long before Indonesia exists and has been the law that sticks to the traditional people itself. In consequence the occurrence of traditional law runs in harmony because it is a responsive law that means that it is the law that is needed by the community. Nowadays, the traditional laws that exists are complex and has many variations between one region and other regions because we know many traditional communities. Along with the development of the state structure, than as juridical formal, since August 17, 1945, Indonesia was created. The occurrence of traditional laws were started to be used in the ordinance or Indonesian positive law.In Base Ordinance of 1945 (UUD 1945), is not written in a section but is said in the moving of section II, as it is in the Temporary Ordinance of 1950 (UUDS 1950 and in the organic law, for example, in the Ordinance no 5, 1960 about UUPA. This shows that the status of traditional law has its high place in the level of the state structure in the Republic of Indonesia. The value of the traditional law, for example; the horizontal separation, the right of traditional law in the society, the variation in the relationship is enriching the traditional law itself. And until now it is still raised up by the community itself as the special traditional law.